2019
DOI: 10.1142/s1793525319500250
|View full text |Cite
|
Sign up to set email alerts
|

Marked length rigidity for one-dimensional spaces

Abstract: In a compact geodesic metric space of topological dimension one, the minimal length of a loop in a free homotopy class is well-defined, and provides a function l : π 1 (X) −→ R + ∪ ∞ (the value ∞ being assigned to loops which are not freely homotopic to any rectifiable loops). This function is the marked length spectrum. We introduce a subset Conv(X), which is the union of all non-constant minimal loops of finite length. We show that if X is a compact, non-contractible, geodesic space of topological dimension … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…2 Therefore, it is logical to study the only non-trivial homotopy group, the fundamental group π 1 (G). Second, Constantine and Lafont (Constantine and Lafont 2018) showed that the length spectrum of a graph determines a certain subset of it up to isomorphism. Thus, we aim to determine when two graphs are close to each other by comparing their length spectra relying on the main theorem of (Constantine and Lafont 2018).…”
Section: Length Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…2 Therefore, it is logical to study the only non-trivial homotopy group, the fundamental group π 1 (G). Second, Constantine and Lafont (Constantine and Lafont 2018) showed that the length spectrum of a graph determines a certain subset of it up to isomorphism. Thus, we aim to determine when two graphs are close to each other by comparing their length spectra relying on the main theorem of (Constantine and Lafont 2018).…”
Section: Length Spectrummentioning
confidence: 99%
“…In this work we use cycle and closed path interchangeably. 4 In (Constantine and Lafont 2018), the authors need an isomorphism between the fundamental group of the spaces that are being compared, which is also computationally prohibitive. 5 Here we choose both EMD and r = r 0 based on the experimental evidence of Fig.…”
Section: Endnotesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work [10,40] has shown that the two-cores extracted from two graphs are isomorphic when the set of all nonbacktracking cycles in each graph are equal (this is referred to as the length spectrum). This means that should we be able to enumerate all possible non-backtracking cycles we can effectively compare two graph structures.…”
Section: Distributional Non-backtracking Spectral Distancementioning
confidence: 99%
“…Several works extended this result to more general types of metrics: to surfaces without conjugate points in [CFF92] and [Fat89], translation surfaces in [DLR10], flat surfaces with cone points in [BL18], and the combination of the previous cases in [Con18] . The marked length spectrum rigidity question has been studied in other contexts as well: in locally symmetric spaces of negative curvature in [Ham90], projective geometries in [Kim01] and [CD10], Fuchsian buildings in [CL19b], and 1-dimensional spaces in [CL19a].…”
Section: Introductionmentioning
confidence: 99%